PENGARUH PROMOSI JABATAN TERHADAP KEPUASAN KERJA MELALUI PRESTASI KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN TVRI LAMPUNG - Betty Magdalena; Okta Rulyati (Jurnal Bisnis Darmajaya, 2019)
The objective of this research was finding out the effect of the staff achievement on job satisfaction through promotion as the intervening variable in TVRI Lampung. The type of this research was the quantitative research with associative method. The exogenous variable used in this research was the staff achievement; the endogenous variable was the job satisfaction; and, the intervening variable was the promotion. The population of this research was the staffs of TVRI Lampung. A number of the population of this research was 102 respondents. A number of samples used in this research were 81 respondents. The sampling technique used in this research was Stratified Random Sampling. The data collecting technique used in this research was distributing the questionnaire directly to the respondents. The data analysis technique used in this research was the path analysis. The result of this research showed that staff achievement affected the job satisfaction; the achievement affected promotion; the promotion affected the job satisfaction; and, the achievement affected the job satisfaction through promotion. Keywords - Staff Achievement, Job Satisfaction, Promotion